2009
DOI: 10.1057/thr.2009.22
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study Identifying Soft Skill Competencies in Entry-Level Managers

Abstract: The identification of competencies needed by hospitality managers has been investigated since the 1980s. In all of the competency research related to hospitality management, essential competencies include skills that can be classified as soft skills, yet a comprehensive list of these soft skills has not been identified. The purpose of this project is to have industry professionals rate the importance of soft skill competencies found in literature, and then reduce this list of competencies by completing a facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(113 citation statements)
references
References 20 publications
(15 reference statements)
2
88
0
11
Order By: Relevance
“…On the other hand, display of political behavior in organizations is considered as the source of stress, conflict, poor performance, physical and mental intention to leave the work, burnout, ineffective communication with manager or supervisor, and finally it reduces organizational commitment (Weber et al, 2009). The results of current research indicated that majority of headquarters employees in Tehran University of Medical Sciences had low tendency to display political behavior in their organization.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…On the other hand, display of political behavior in organizations is considered as the source of stress, conflict, poor performance, physical and mental intention to leave the work, burnout, ineffective communication with manager or supervisor, and finally it reduces organizational commitment (Weber et al, 2009). The results of current research indicated that majority of headquarters employees in Tehran University of Medical Sciences had low tendency to display political behavior in their organization.…”
Section: Discussionmentioning
confidence: 73%
“…The results of some previous studies indicate that tendency to political behavior in organizations reduces employees' organizational commitment, lay off, work aversion, and avoiding effective communication, have negative impact on their performance (Rahman Seresht, & Fayazi, 2009;Weber et al, 2009). In addition, the direct impact of employees' perceptions from the political environment can be effective in their degree of commitment aversion (Rahimnia & Hasanzadeh, 2010).…”
mentioning
confidence: 99%
“…Gains power to exercise influence over others). Prior research on the 107 competencies has been conducted (Weber, Finley, Crawford, & Rivera, 2009). These researchers placed the competencies into seven categories.…”
Section: Methodsmentioning
confidence: 99%
“…The two panels will evaluate a list of soft skill competencies found in literature (Weber, Finley, Crawford, and Rivera, 2009). By studying the soft skills essential to success in the business environment, a company can 1) improve their selection process, 2) enhance their initial training process, 3) improve their development program, 4) strengthen the performance evaluation process, and hopefully 5) reduce turnover.…”
Section: Introductionmentioning
confidence: 99%
“…Hard skills are often referred to as technical skills (such as dealing with data and administrative skills); soft skills are behavioral skills or people skills which are needed to apply technical skills in the workplace. The latter are especially important for entry-level managers (Weber et al, 2009). Robles (2012) emphasized another element of soft skills, i.e., personal qualities and career attributes, such as professionalism and integrity.…”
Section: The Importance Of Soft Skills For University Graduates' Emplmentioning
confidence: 99%